Assessment of optic disc parameter changes in head and neck cancer patients undergoing radiotherapy based on OCT - Liu, Rui; Chen, Pengfei; Zhao, Keren; Wang, Han; Zhao, Ping; Su, Yudan (Frontiers in Oncology, 2026)
BackgroundRadiotherapy to the head and neck is an important treatment modality for malignant head and neck tumors, but it often leads to various ocular complications, including optic neuropathy. The optic disc, as a key part of the visual conduction pathway, is an important indicator for evaluating radiation-related ocular complications. Optical coherence tomography (OCT) can provide detailed structural information of the retina and optic disc, which is helpful for early detection of minor structural changes in the optic disc.MethodsThis study is a prospective cross-sectional study, including 60 healthy examinees and 60 patients with malignant head and neck tumors. All patients underwent OCT examinations before radiotherapy, at the end of radiotherapy, and 3 and 6 months after radiotherapy. OCT was used to measure optic disc parameters such as retinal nerve fiber layer thickness (RNFL) and choroidal vascular index (CVI). Radiotherapy was performed using a megavoltage linear accelerator for external irradiation, following a conventional high-dose fractionation regimen. Statistical analysis was conducted using SPSS software, with Mann-Whitney U test and t-test used to compare differences between the two groups.ResultsA total of 120 participants were included in the study. Radiotherapy had a significant impact on macular thickness (MT) in different regions and time points. The lateral nasal macular thickness significantly thinned 3 and 6 months after radiotherapy (P<0.001). The CVI significantly decreased 3 and 6 months after radiotherapy (P = 0.0642 and P = 0.0119), indicating that radiotherapy may affect choroidal microcirculation. RNFL did not show significant differences before and after radiotherapy and during follow-up, but some regions showed significant changes after radiotherapy, such as the inner nasal and inner inferior RNFL thicknesses, which were significantly different 6 months after radiotherapy (P = 0.0109 and P = 0.0187).ConclusionsRadiotherapy to the head and neck can lead to significant changes in the structure of the optic disc, especially in choroidal microcirculation and some retinal regions. OCT, as a non-invasive imaging technique, can detect these changes early and provide a basis for early intervention by clinicians to reduce the impact of radiation-related ocular complications on patients’ visual function. Future studies should further explore the potential effects of radiotherapy on optic disc function and assess the effects of preventive and therapeutic interventions.